Market Structure and Innovation: A Survey - Kamien, Morton I.; Schwartz, Nancy L. (Journal of Economic Literature, 2016)
ECONOMICS, we all recite, deals with allocation of limited resources towards satisfaction of unlimited wants. Resources are typically identified as land, labor, and capital plus a technology that determines their transformation into consumer goods. Disparity between the available goods and services and the desired gives rise to scarcity and the question of what, how, and for whom to produce. The focus then shifts to description and evaluation of alternative resource allocation mechanisms for making the choices. The Pareto criterion, by which an allocation of resources is deemed efficient if any reallocation improving the position of some individual worsens the position of others, is a commonly employed gauge of a mechanism's performance. In the absence of externalities, increasing returns to scale, and uncertainty, a perfectly competitive market system yields a Pareto optimal allocation of resources; this underlies the view that individual self-interest is compatible with society's interest. The further conclusion that Pareto optimality may not be achieved via the market system in the presence of monopoly elements provides an economic rationale for antitrust laws. The objective of a resource allocation mechanism appears to be, according to the analysis described above, to make the best of available resources. The alternative objective of relaxing constraints through expanding the resource base or developing new technology seems to be beyond its scope. Thus, until rather recently, technical advance had been regarded, in the mainstream of economic theory, as unmotivated by the quest for profits and substantially unaffected by resource allocation. Instead, as J. Schmookler observed, technology had been viewed as a parameter like the weather, affecting the outcome of resource allocations but itself unaffected by them [84, 1965]. Evidence that technological progress has significantly contributed to growth in productivity, together with a substantial increase in research and development activity, largely financed by government and carried out by industry (see F. Machlup [51, 1962]), may have spurred reconsideration of this view. Once technical advance is regarded as an economic variable, it is natural to in-